Art and the Politics of the Body - Clay, Megan (Feminist theology, 2015)
The female body whether it be child or woman has in the past and in the present struggled for human equality on multiple levels. There have of course been changes but the socio-political boundaries still shift this way and that under the weight of unequal power relations between genders within the ever unfolding fields of patriarchy. Sometimes it seems there are moments of clarity of achieved equality but more often than not the reality is hidden under a pseudo agenda of token offerings. This is a battle that continues within the fields of economics, politics and the language that defines the status quo of the feminine. Feminist liberation theologies as we know begin with the experience of women and as women expand their experience and education through the worlds of politics, economics in academia, the church and other institutions so does the awareness of their subjugation to heteronormative values both past and present. Art has a way of expressing something that the word cannot, this is the language of feeling and emotion. Emotions and feelings have been historically allocated materially to women as a chaotic assemblage that does not fit into the rational world of men. I argue that feminist art describes powerfully the effect patriarchal power has had over female bodies through both personal and collective experiences and that is without doubt a political matter.